2009
DOI: 10.1371/journal.pone.0007952
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serotonin via 5-HT2B Receptors in the Reinforcing Effects of MDMA in Mice

Abstract: The amphetamine derivative 3,4-methylenedioxymethamphetamine (MDMA, ecstasy) reverses dopamine and serotonin transporters to produce efflux of dopamine and serotonin, respectively, in regions of the brain that have been implicated in reward. However, the role of serotonin/dopamine interactions in the behavioral effects of MDMA remains unclear. We previously showed that MDMA-induced locomotion, serotonin and dopamine release are 5-HT2B receptor-dependent. The aim of the present study was to determine the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 54 publications
(68 reference statements)
2
51
0
2
Order By: Relevance
“…It is noteworthy that 5-HT 2B receptors have been shown to modulate aspects of both serotonergic and dopaminergic neurotransmission (Bevilacqua et al, 2010;Diaz and Maroteaux, 2011;Doly et al, 2008). In particular, ex vivo studies have indicated that 5-HT 2B receptors may serve as positive autoregulator of the serotonergic tone through modulating the 5-HT transporter (SERT) in raphe neurons (Launay et al, 2006), and in vivo studies in mice further confirmed that 5-HT 2B receptors contribute to the behavioral effects of the SERT-targeting 5-HT releasers, MDMA (ie, ecstasy) and dexfenfluramine (Banas et al, 2011;Doly et al, 2009;Doly et al, 2008). Recently, Auclair et al (2010) reported that 5-HT 2B receptors control the mesoaccumbal DA pathway activity, as an acute systemic administration of the 5-HT 2B subtype-selective antagonist RS127445 in rats induced a region-selective reduction of extracellular DA levels in the NAC in response to amphetamine challenge.…”
Section: Per Group) In the Latent Inhibition (Li) Paradigm (E) LI Wmentioning
confidence: 95%
“…It is noteworthy that 5-HT 2B receptors have been shown to modulate aspects of both serotonergic and dopaminergic neurotransmission (Bevilacqua et al, 2010;Diaz and Maroteaux, 2011;Doly et al, 2008). In particular, ex vivo studies have indicated that 5-HT 2B receptors may serve as positive autoregulator of the serotonergic tone through modulating the 5-HT transporter (SERT) in raphe neurons (Launay et al, 2006), and in vivo studies in mice further confirmed that 5-HT 2B receptors contribute to the behavioral effects of the SERT-targeting 5-HT releasers, MDMA (ie, ecstasy) and dexfenfluramine (Banas et al, 2011;Doly et al, 2009;Doly et al, 2008). Recently, Auclair et al (2010) reported that 5-HT 2B receptors control the mesoaccumbal DA pathway activity, as an acute systemic administration of the 5-HT 2B subtype-selective antagonist RS127445 in rats induced a region-selective reduction of extracellular DA levels in the NAC in response to amphetamine challenge.…”
Section: Per Group) In the Latent Inhibition (Li) Paradigm (E) LI Wmentioning
confidence: 95%
“…Male Sprague-Dawley rats (Janvier, and a selectivity for this receptor 1,000 times stronger than that for other receptors and monoamine uptake sites [12,19,20]. A 1 mg/ml stock solution of RS127445 was prepared in DMSO.…”
Section: Animals and Ethics Statementsmentioning
confidence: 99%
“…Understanding the genetic bases of drug abuse vulnerability and particular allelic variants that contribute to this vulnerability can strongly improve our understanding of human addictions. We have recently extended the role of serotonin (5-HT) in the behavioral responses to psychostimulants by revealing that the genetic ablation of Htr 2B in mice, the gene encoding 5-HT 2B receptors, eliminates locomotor response and place preference induced by MDMA [(6)-3,4-methylenedioxymethamphetamine] (Doly et al, 2008(Doly et al, , 2009). Independently, three novel single nucleotide polymorphisms, two of which result in a point mutation, were described in a drug-abusing population (Lin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%